INFLUENCE OF USE FLUID WARMER TO REDUCING THE EVENT OF SHIVERING IN PATIENTS WITH POST SPINAL ANESTHESIA - Sutrisno, Sutrisno; Mumpuni, Lia Wikanova; Dwianggimawati, Mayta Sari (LPPM STIKes SATRIA BHAKTI NGANJUK, 2022)
Post anesthetic shivering (PAS) or shivering after anesthesia is defined as a fasciculation of the skeletal muscles in the face, head, jaw, trunk, or extremities that lasts more than fifteen seconds. The research design used in this study was a quasy experiment with a control group. With a sample size of 30 respondent. The mean pre and post temperature of the intervention group was (36.4±0.79 and 36.25±1.17) while the mean pre and post temperature of the control group was (36.51±0.71 and 35.17±1.35). The results of the incidence of shivering in the intervention group respondents were found to be the largest in the non-shivering category as many as 8 (53.3%) respondents, while in the control group the largest in the category of muscular activity in general throughout the body there was 6 (40%) respondents. The results of the Independent T Test obtained a p value of 0.014, while the Mann Whitney test obtained a p value of 0.037 so there was a significant difference in the patient's temperature and the incidence of shivering in patients after spinal anesthesia being given a warm infusion.